Analysis of Student Affairs Management in Character Development Based on Al-Islam and Muhammadiyah Values - Riska Aoliya Sari; Nurul Latifatul Inayati (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study aims to analyze the implementation of student affairs management in character development based on Al-Islam and Muhammadiyah (AIK) values at SMA Muhammadiyah 1 Surakarta and to identify its supporting factors and challenges. The study employed a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observations of student activities and religious habituation, and documentation, and analyzed thematically using data reduction, display, and conclusion drawing. The results indicate that the integration of student affairs management with AIK values significantly contributes to the development of students’ religious character, discipline, responsibility, and social awareness. Implementation is carried out through integrated programs, religious habituation, and continuous supervision. However, challenges include coordination issues and limited research scope. Mitigation efforts involve strengthening collaboration among schools, parents, and innovative educational programs. The findings highlight that student affairs management serves as a strategic instrument in strengthening value-based school culture in the Society 5.0 era.